More Filtering on SNP Calling Does Not Remove Evidence of Inter-Nucleus Recombination in Dikaryotic Arbuscular Mycorrhizal Fungi - Chen, Eric C. H.; Mathieu, Stephanie; Hoffrichter, Anne; Ropars, Jeanne; Dreissig, Steven; Fuchs, Jörg; Brachmann, Andreas; Corradi, Nicolas (Frontiers in Plant Science, 2020)
Evidence for the existence of dikaryote-like strains, low nuclear sequence diversity and inter-nuclear recombination in arbuscular mycorrhizal fungi has been recently reported based on single nucleus sequencing data. Here, we aimed to support evidence of inter-nuclear recombination using an approach that filters SNP calls more conservatively, keeping only positions that are exclusively single copy and homozygous, and with at least 5 reads supporting a given SNP. This methodology recovers hundreds of putative inter-nucleus recombination events across publicly available sequence data from individual nuclei. Challenges related to the acquisition and analysis of sequence data from individual nuclei are highlighted and discussed, and ways to address these issues in future studies are presented.